Commercial Coopetition: Forms, Tensions and Managerial Perspectives - Jaouen, Annabelle; Pellegrin-Boucher, Estelle (Management international / International Management / Gestiòn Internacional, 2022)
Commercial coopetition consists of cooperating with competitors in customer-like activities. This strategy has developed substantially in recent years but has been little studied in the literature. This research aims to analyze the forms of commercial coopetition and the tensions it generates to understand the sources of blockage and propose management devices. To do so, we deploy a qualitative research protocol based on 23 semi-directive interviews with directors of alliances and partnerships. The research results reveal two forms of commercial coopetition that create five types of inter- and intraorganizational tensions and we identify three ways of managing these tensions.